2020
DOI: 10.24940/theijhss/2020/v8/i5/hs2005-006
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Monitoring and Evaluation Adoption on Implementation of County Government Sponsored Projects in Rabai Sub-County, Kenya

Abstract: In Kenya, County Governments are mandated to carry out development projects anchored on their County Integrated Development Plans (CIDPs). The implementations of these projects have been met by higher number of failures. However, irrespective of the outcome of the projects, the aspect of Monitoring and Evaluation (M&E) is rarely cited in relation to the outcome. The objectives of conducting Evaluations is to determine the relevance and realization of project objectives, efficiency and effectiveness levels of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…According to Onyango (2017), most of the projects in Kirinyaga County are done without stakeholder involvement. This has resulted to lesser benefit to the locals since many of these https://doi.org/10.53819/81018102t4213 projects initiated have not been completed.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…According to Onyango (2017), most of the projects in Kirinyaga County are done without stakeholder involvement. This has resulted to lesser benefit to the locals since many of these https://doi.org/10.53819/81018102t4213 projects initiated have not been completed.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Quality Management Practices improve project planning, management, and execution efficiency, hence project success (Ibrahim,& Daniel, 2019). Quality implementation on infrastructural projects, programs are lacking in the county governments, leading to unsatisfactory projects for the residents (Galgallo, 2019)…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…In the context of project performance, previous studies have established a positive relationship between the utilization of M&E information and project outcomes. Studies conducted in Kenya have found that the utilization of M&E information has a significant effect on the performance of projects in various organizations [8,9,10].…”
Section: Introductionmentioning
confidence: 99%